1987
DOI: 10.1016/s0735-1097(87)80397-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diltiazem and nifedipine alone and in combination in patients with coronary artery spasm

Abstract: Fifteen patients with coronary artery spasm completed a double-blind placebo-controlled trial comparing diltiazem and nifedipine. Increasingly, higher daily doses (diltiazem, 90 to 360 mg; nifedipine, 30 to 120 mg) were administered to achieve optimal clinical effects. Daily diaries and ambulatory electrocardiographic recordings were used to assess efficacy and side effects. Both drugs significantly decreased angina frequency compared with that in the preceding placebo period (diltiazem 1.4 +/- 0.4 [mean +/- S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…They further showed that provoked coronary spasm was the strongest predictor of MACE during the follow-up [16]. CCBs have been shown to be highly effective in suppressing coronary spasms and improve the prognosis of patients with coronary spasms [1,2,10,11,17,18]. CCBs, however, had not been given to the majority of the patients with provoked spasms in the study of Wakabayashi et al [16].…”
Section: Discussionmentioning
confidence: 99%
“…They further showed that provoked coronary spasm was the strongest predictor of MACE during the follow-up [16]. CCBs have been shown to be highly effective in suppressing coronary spasms and improve the prognosis of patients with coronary spasms [1,2,10,11,17,18]. CCBs, however, had not been given to the majority of the patients with provoked spasms in the study of Wakabayashi et al [16].…”
Section: Discussionmentioning
confidence: 99%
“…7) In some settings, coronary spasm is refractory to vasodilating agents and induces malignant arrhythmia and circulatory collapse. To treat this condition, many medications such as magnesium Rho-kinase inhibitors 8) or nifedipine 9) have been proposed. Stent implantation is also considered being an option.…”
Section: Discussionmentioning
confidence: 99%
“…Zaiac, et al 6) reported the usefulness of intravenous nifedipine for the refractory coronary spasm after CABG. Prida, et al 7) also reported the combination of nifedipine and diltiazem for patients with coronary spasm which was resistant to single drug treatment. Thus, the additional use of nifedipine for resolving the spasm should be attempted.…”
Section: Discussionmentioning
confidence: 99%